Understanding the Lived Experiences of Perfectionism and Job Burnout Among IT Employees: A Qualitative Study - Anushka Singh; Dr. Neelam Pandey (International Journal of Indian Psychȯlogy, 2025)
This study explores the dual-edged relationship between perfectionism and burnout among IT professionals, examining how high-performance standards influence well-being and productivity. Through qualitative analysis of interview responses from 15 IT workers across leading firms (e.g., Google, Amazon, Meta), the research identifies perfectionism as a culturally ingrained norm, characterized by relentless pursuit of error-free work (100% prevalence) and self-imposed high standards (93%). While perfectionism enhances output quality (100%) and professional satisfaction (80%), it simultaneously contributes to chronic stress (100%), missed deadlines (87%), and burnout manifestations—including emotional exhaustion (100%) and physical symptoms like migraines (93%). Workplace stressors such as unrealistic expectations (100%) and ineffective work-life balance policies (87%) further exacerbate burnout. Although individuals employ coping strategies like mindfulness (60%) and social support (73%), organizational support remains insufficient, with only 47% of participants finding mental health initiatives effective. The study underscores the need for systemic interventions, including redefined performance metrics, leadership training, and enforceable work-life boundaries, to mitigate burnout while sustaining productivity. These findings offer actionable insights for IT organizations aiming to balance operational excellence with employee well-being.